Behavior and exocrine glands in the myrmecophilous beetle Dinarda dentata (Gravenhorst, 1806) (Coleoptera: Staphylinidae: Aleocharinae). - Bert Hölldobler; Christina L Kwapich (PLoS ONE, 2019)
The nests of advanced eusocial ant species can be considered ecological islands with a diversity of ecological niches inhabited by not only the ants and their brood, but also a multitude of other organisms adapted to particular niches. In the current paper, we describe the myrmecophilous behavior and the exocrine glands that enable the staphylinid beetle Dinarda dentata to live closely with its host ants Formica sanguinea. We confirm previous anecdotal descriptions of the beetle's ability to snatch regurgitated food from ants that arrive with a full crop in the peripheral nest chambers, and describe how the beetle is able to appease its host ants and dull initial aggression in the ants.